High-hardness card paper and manufacturing process thereof
By optimizing the formula and process parameters of the raw material, preparing high -hardness card paper, solving the problem of insufficient corrosion resistance and corrosion resistance of traditional cards, and realizing the significant hardness improvement and corrosion resistance of card paper. Application scenarios and have the advantages of environmental protection and cost benefits.
Patent Information
- Application Number
- CN202411744698.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional card papers do not perform well in terms of hardness, are difficult to meet the needs of high-strength use and long-term storage, and are insufficient corrosion resistance in special environments.
By optimizing the formula and manufacturing process, the use of pulp, chitosan, acetic acid, acetone, sodium hydroxide, chloride, isopropyl, methanol, polyetherine, nanocarium graphene, boron nitrogen, and other ingredients are prepared Type card paper, through multi -step process such as basic card paper preparation, carboxymethyling base shell synthesis, shell polyethylene closer polyethamine preparation and impregnation solidification, etc., to improve the hardness and corrosion resistance of card paper.
It significantly improves the hardness and corrosion resistance of card paper. It can maintain stable performance in high -intensity and harsh environments. It is suitable for diversified application scenarios.
Smart Images

Figure CN119372956A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material science and technology, and in particular to a high-hardness card paper and a manufacturing process thereof. Background Art
[0002] In today's society, cards are a common entertainment and cultural product with an increasingly wide range of applications, from traditional game cards to various collectible cards, display cards, etc. With the continuous expansion of card application scenarios and the gradual improvement of consumers' requirements for card quality, higher requirements are placed on the performance of card paper.
[0003] Traditional card paper often performs poorly in terms of hardness and is difficult to meet the requirements of high-intensity use and long-term storage. In actual use, it is prone to wear and tear, which affects the service life and appearance of the cards. At the same time, in some special environments, such as humid and acidic conditions, the corrosion resistance of traditional card paper is also insufficient, resulting in a decrease in its performance.
[0004] In order to meet the market demand for high-quality card paper, it is imperative to develop a card paper with high hardness and good corrosion resistance. This requires not only innovation in the selection of raw materials, but also optimization of the manufacturing process to achieve a significant improvement in the performance of card paper and meet consumers' demand for high strength, high durability and diversified application scenarios of card paper. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] In view of the shortcomings of the prior art, the present invention provides a high-hardness card paper and its manufacturing process, which solves the problem that traditional card paper often performs poorly in hardness and is difficult to meet the requirements of high-intensity use and long-term storage. In actual use, it is easy to cause wear and tear, which affects the service life and aesthetics of the card.
[0007] (II) Technical solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] A high-hardness card paper comprises the following raw materials in parts by weight: 20-30 parts of pulp, 5-8 parts of chitosan, 28-40 parts of acetic acid, 11-12 parts of acetone, 4-5 parts of sodium hydroxide, 5-6 parts of chloroacetic acid, 16-17 parts of isopropanol, 100 parts of methanol, 5-6 parts of polyetheramine, 1.5-2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 3-4 parts of N-hydroxysuccinimide, 3.5-4 parts of meta-phenylenediamine, 10-11 parts of epoxy resin, 7.5-8 parts of urea formaldehyde resin, 4-5 parts of nano-scale graphene, 2.5-3 parts of boron nitride, 1.5-2 parts of thickener and 200-250 parts of deionized water.
[0010] Preferably, the thickener is composed of coconut diethanolamide, PEG-150 distearate, and fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 1:1:1.
[0011] Preferably, the following components are included in parts by weight: 25 parts of pulp, 6 parts of chitosan, 34 parts of acetic acid, 11.5 parts of acetone, 4.5 parts of sodium hydroxide, 5.5 parts of chloroacetic acid, 16.5 parts of isopropanol, 100 parts of methanol, 5.5 parts of polyetheramine, 1.8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 3.5 parts of N-hydroxysuccinimide, 3.8 parts of meta-phenylenediamine, 10.5 parts of epoxy resin, 7.8 parts of urea formaldehyde resin, 4.5 parts of nano-graphene, 2.8 parts of boron nitride, 1.8 parts of thickener, and 220 parts of deionized water.
[0012] Preferably, the following components are included in parts by weight: 28 parts of pulp, 7 parts of chitosan, 38 parts of acetic acid, 11.8 parts of acetone, 4.8 parts of sodium hydroxide, 5.8 parts of chloroacetic acid, 16.8 parts of isopropanol, 100 parts of methanol, 5.8 parts of polyetheramine, 1.9 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 3.8 parts of N-hydroxysuccinimide, 3.9 parts of meta-phenylenediamine, 10.8 parts of epoxy resin, 7.9 parts of urea formaldehyde resin, 4.8 parts of nano-graphene, 2.9 parts of boron nitride, 1.9 parts of thickener, and 240 parts of deionized water.
[0013] A manufacturing process of high-hardness card paper comprises the following steps:
[0014] S1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 min, then add nano-graphene, boron nitride and thickener, stir at a speed of 350 rpm for 2.5 h, and obtain basic card paper after drying; wherein the weight ratio of nano-graphene, boron nitride and thickener is 1:0.8:0.5;
[0015] S2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after they are completely dissolved, and obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350 rpm and 75°C, slowly add chloroacetic acid dropwise, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol, and dry to obtain carboxymethyl chitosan;
[0016] S3: Add polyetheramine and deionized water to a new reactor, stir at 350 rpm, add carboxymethyl chitosan obtained in S2, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and N-hydroxysuccinimide after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0017] S4: Add m-phenylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in S3 and stir at 250 rpm for 2.5 hours. Immerse the basic card paper obtained in S1 and cure it at 150°C for 2 hours to obtain the finished product.
[0018] Preferably: in S1, the drying temperature is 80-90° C. and the drying time is 3-4 hours.
[0019] Preferably: in S2, the speed of adding chloroacetic acid dropwise is 0.5-0.8 ml per minute.
[0020] Preferably: in S3, the mass ratio of polyetheramine, carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide is 1:0.8:0.2:0.3.
[0021] Preferably: in S4, the mass ratio of m-xylylenediamine, epoxy resin, urea formaldehyde resin and chitosan grafted polyetheramine is 1:3:2:1.5.
[0022] Preferably, in S4, the base card paper is immersed in the mixed solution for 1-2 hours.
[0023] (III) Beneficial effects
[0024] 1. Significantly improve the hardness of card paper: By optimizing the raw material formula and process parameters, especially adding a specific proportion of nano-graphene, boron nitride, chitosan grafted polyetheramine and other ingredients, the prepared card paper has a higher tear resistance index and meets the demand for high hardness.
[0025] 2. Enhanced corrosion resistance: After soaking in a 10% hydrochloric acid solution for 24 hours, the surface of the card paper still has no obvious changes, showing good corrosion resistance and being able to maintain stable performance in harsh environments.
[0026] 3. Green raw materials and processes: Most of the raw materials used in the entire manufacturing process are environmentally friendly and harmless, and the process conditions are relatively mild, which meets the requirements of sustainable development.
[0027] 4. Strong process operability: The manufacturing process steps described in each embodiment are clear, the parameters are clear, and it is easy to operate and control in actual production, which is conducive to large-scale industrial production.
[0028] 5. Stable and reliable performance: Through comparative tests of multiple embodiments and control examples, it is proved that the high-hardness card paper prepared by the invention has stable performance and is not easily affected by slight changes in raw materials and process fluctuations.
[0029] 6. Expand application areas: Due to its high hardness and good corrosion resistance, this card paper can be used in more fields that have special requirements on paper performance, such as high-end card making, special packaging, etc.
[0030] 7. Good cost-effectiveness: While ensuring high performance, through reasonable raw material selection and process optimization, production costs can be controlled and the market competitiveness of products can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.
[0032] Figure 1 It is a schematic diagram of the components of the card paper in the present invention. DETAILED DESCRIPTION
[0033] With the development of society and the advancement of science and technology, the performance requirements for card paper are getting higher and higher, especially in terms of hardness. Traditional card paper often cannot meet the requirements of high strength and high hardness. The present invention aims to provide a high-hardness card paper and a manufacturing process thereof, which can significantly improve the hardness and comprehensive performance of the card paper by optimizing the raw material formula and process parameters.
[0034] The high-hardness card paper of the present invention is composed of pulp, chitosan, acetic acid, acetone, sodium hydroxide, chloroacetic acid, isopropyl alcohol, methanol, polyetheramine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, meta-xylylenediamine, epoxy resin, urea formaldehyde resin, nano-scale graphene, boron nitride, thickener and deionized water in a specific proportion. Its manufacturing process includes multiple steps, such as preparing basic card paper, synthesizing carboxymethyl chitosan, preparing chitosan grafted polyetheramine, impregnation and curing, etc.
[0035] In order to verify the effect of the present invention, the following multiple examples were carried out and control experiments were set up:
[0036] Embodiment 1:
[0037] Raw materials preparation:
[0038] Pulp: 20 parts;
[0039] Chitosan: 5 parts;
[0040] Acetic acid: 28 parts;
[0041] Acetone: 11 parts;
[0042] Sodium hydroxide: 4 parts;
[0043] Chloroacetic acid: 5 parts;
[0044] Isopropyl alcohol: 16 parts;
[0045] Methanol: 100 parts;
[0046] Polyetheramine: 5 parts;
[0047] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.5 parts;
[0048] N-hydroxysuccinimide: 3 parts;
[0049] Meta-phenylenediamine: 3.5 parts;
[0050] Epoxy resin: 10 parts;
[0051] Urea formaldehyde resin: 7.5 parts;
[0052] Nanoscale graphene: 4 parts;
[0053] Boron nitride: 2.5 parts;
[0054] Thickener: 1.5 parts;
[0055] Deionized water: 200 parts.
[0056] Manufacturing process:
[0057] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add nano-graphene, boron nitride, and a thickener, stir at a speed of 350 rpm for 2.5 hours, and dry at 85° C. for 3.5 hours to obtain basic card paper;
[0058] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.6 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0059] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0060] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3 and stir at 250 rpm for 2.5 hours. Immerse the basic card paper obtained in step 1 for 1.5 hours. After taking it out, cure it at 150°C for 2 hours to obtain the finished product.
[0061] Embodiment 2:
[0062] Raw materials preparation:
[0063] Pulp: 25 parts;
[0064] Chitosan: 6 parts;
[0065] Acetic acid: 34 parts;
[0066] Acetone: 11.5 parts;
[0067] Sodium hydroxide: 4.5 parts;
[0068] Chloroacetic acid: 5.5 parts;
[0069] Isopropyl alcohol: 16.5 parts;
[0070] Methanol: 100 parts;
[0071] Polyetheramine: 5.5 parts;
[0072] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.8 parts;
[0073] N-hydroxysuccinimide: 3.5 parts;
[0074] Meta-xylylenediamine: 3.8 parts;
[0075] Epoxy resin: 10.5 parts;
[0076] Urea formaldehyde resin: 7.8 parts;
[0077] Nano-graphene: 4.5 parts;
[0078] Boron nitride: 2.8 parts;
[0079] Thickener: 1.8 parts;
[0080] Deionized water: 220 parts.
[0081] Manufacturing process:
[0082] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add nano-graphene, boron nitride, and a thickener, stir at a speed of 350 rpm for 2.5 hours, and dry at 88° C. for 3 hours to obtain basic card paper;
[0083] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.7 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0084] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0085] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3, stir at 250 rpm for 2.5 hours, immerse the basic card paper obtained in step 1 for 1.8 hours, take it out and cure it at 150°C for 2 hours to obtain the finished product.
[0086] Embodiment 3:
[0087] Raw materials preparation:
[0088] Pulp: 28 parts;
[0089] Chitosan: 7 parts;
[0090] Acetic acid: 38 parts;
[0091] Acetone: 11.8 parts;
[0092] Sodium hydroxide: 4.8 parts;
[0093] Chloroacetic acid: 5.8 parts;
[0094] Isopropyl alcohol: 16.8 parts;
[0095] Methanol: 100 parts;
[0096] Polyetheramine: 5.8 parts;
[0097] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.9 parts;
[0098] N-hydroxysuccinimide: 3.8 parts;
[0099] Meta-phenylenediamine: 3.9 parts;
[0100] Epoxy resin: 10.8 parts;
[0101] Urea formaldehyde resin: 7.9 parts;
[0102] Nanoscale graphene: 4.8 parts;
[0103] Boron nitride: 2.9 parts;
[0104] Thickener: 1.9 parts;
[0105] Deionized water: 240 parts.
[0106] Manufacturing process:
[0107] Step 1: Add pulp and deionized water into a reactor, stir at 400 rpm for 50 min, then add nano-graphene, boron nitride and thickener, stir at 350 rpm for 2.5 h, and dry at 90° C. for 3 hours to obtain basic card paper;
[0108] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.75 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0109] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0110] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3, stir at 250 rpm for 2.5 hours, immerse the basic card paper obtained in step 1 for 1.6 hours, take it out and cure it at high temperature at 150°C for 2 hours to obtain the finished product.
[0111] Embodiment 4:
[0112] Raw materials preparation:
[0113] Pulp: 30 parts;
[0114] Chitosan: 8 parts;
[0115] Acetic acid: 40 parts;
[0116] Acetone: 12 parts;
[0117] Sodium hydroxide: 5 parts;
[0118] Chloroacetic acid: 6 parts;
[0119] Isopropyl alcohol: 17 parts;
[0120] Methanol: 100 parts;
[0121] Polyetheramine: 6 parts;
[0122] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 2 parts;
[0123] N-hydroxysuccinimide: 4 parts;
[0124] Meta-phenylenediamine: 4 parts;
[0125] Epoxy resin: 11 parts;
[0126] Urea formaldehyde resin: 8 parts;
[0127] Nano-graphene: 5 parts;
[0128] Boron nitride: 3 parts;
[0129] Thickener: 2 parts;
[0130] Deionized water: 250 parts.
[0131] Manufacturing process:
[0132] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add nano-graphene, boron nitride, and a thickener, stir at a speed of 350 rpm for 2.5 hours, and dry at 90° C. for 4 hours to obtain basic card paper;
[0133] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.8 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0134] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0135] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3, stir at 250 rpm for 2.5 hours, immerse the basic card paper obtained in step 1 for 2 hours, take it out and cure it at high temperature at 150°C for 2 hours to obtain the finished product.
[0136] Comparative Example 1:
[0137] Raw materials preparation:
[0138] Pulp: 25 parts;
[0139] Chitosan: 6 parts;
[0140] Acetic acid: 34 parts;
[0141] Acetone: 11.5 parts;
[0142] Sodium hydroxide: 4.5 parts;
[0143] Chloroacetic acid: 5.5 parts;
[0144] Isopropyl alcohol: 16.5 parts;
[0145] Methanol: 100 parts;
[0146] Polyetheramine: 5.5 parts;
[0147] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.8 parts;
[0148] N-hydroxysuccinimide: 3.5 parts;
[0149] Meta-xylylenediamine: 3.8 parts;
[0150] Epoxy resin: 10.5 parts;
[0151] Urea formaldehyde resin: 7.8 parts;
[0152] Nano-graphene: 4.5 parts;
[0153] Thickener: 1.8 parts;
[0154] Deionized water: 220 parts.
[0155] Manufacturing process:
[0156] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add nano-graphene and thickener, stir at a speed of 350 rpm for 2.5 hours, and dry at 88° C. for 3 hours to obtain basic card paper;
[0157] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.7 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0158] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0159] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3, stir at 250 rpm for 2.5 hours, immerse the basic card paper obtained in step 1 for 1.8 hours, take it out and cure it at 150°C for 2 hours to obtain the finished product.
[0160] Comparative Example 2:
[0161] Raw materials preparation:
[0162] Pulp: 25 parts;
[0163] Chitosan: 6 parts;
[0164] Acetic acid: 34 parts;
[0165] Acetone: 11.5 parts;
[0166] Sodium hydroxide: 4.5 parts;
[0167] Chloroacetic acid: 5.5 parts;
[0168] Isopropyl alcohol: 16.5 parts;
[0169] Methanol: 100 parts;
[0170] Polyetheramine: 5.5 parts;
[0171] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.8 parts;
[0172] N-hydroxysuccinimide: 3.5 parts;
[0173] Meta-xylylenediamine: 3.8 parts;
[0174] Epoxy resin: 10.5 parts;
[0175] Urea formaldehyde resin: 7.8 parts;
[0176] Boron nitride: 2.5 parts;
[0177] Thickener: 1.8 parts;
[0178] Deionized water: 220 parts.
[0179] Manufacturing process:
[0180] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add boron nitride and a thickener, stir at a speed of 350 rpm for 2.5 hours, and dry at 88°C for 3 hours to obtain basic card paper;
[0181] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.7 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0182] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0183] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3, stir at 250 rpm for 2.5 hours, immerse the basic card paper obtained in step 1 for 1.8 hours, take it out and cure it at 150°C for 2 hours to obtain the finished product.
[0184] Comparative Example 3:
[0185] Raw materials preparation:
[0186] Pulp: 25 parts;
[0187] Chitosan: 6 parts;
[0188] Acetic acid: 34 parts;
[0189] Acetone: 11.5 parts;
[0190] Sodium hydroxide: 4.5 parts;
[0191] Chloroacetic acid: 5.5 parts;
[0192] Isopropyl alcohol: 16.5 parts;
[0193] Methanol: 100 parts;
[0194] Polyetheramine: 5.5 parts;
[0195] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.8 parts;
[0196] N-hydroxysuccinimide: 3.5 parts;
[0197] Meta-xylylenediamine: 3.8 parts;
[0198] Epoxy resin: 10.5 parts;
[0199] Urea formaldehyde resin: 7.8 parts;
[0200] Nano-graphene: 4.5 parts;
[0201] Boron nitride: 2.5 parts;
[0202] Deionized water: 220 parts.
[0203] Manufacturing process:
[0204] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add nano-graphene and boron nitride, stir at a speed of 350 rpm for 2.5 hours, and dry at 88° C. for 3 hours to obtain basic card paper;
[0205] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.7 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0206] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0207] Step 4: Add m-xylylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3, stir at 250 rpm for 2.5 hours, immerse the basic card paper obtained in step 1 for 1.8 hours, take it out and cure it at 150°C for 2 hours to obtain the finished product.
[0208] Comparative Example 4:
[0209] Raw materials preparation:
[0210] Pulp: 25 parts;
[0211] Chitosan: 6 parts;
[0212] Acetic acid: 34 parts;
[0213] Acetone: 11.5 parts;
[0214] Sodium hydroxide: 4.5 parts;
[0215] Chloroacetic acid: 5.5 parts;
[0216] Isopropyl alcohol: 16.5 parts;
[0217] Methanol: 100 parts;
[0218] Polyetheramine: 5.5 parts;
[0219] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: 1.8 parts;
[0220] N-hydroxysuccinimide: 3.5 parts;
[0221] Epoxy resin: 10.5 parts;
[0222] Urea formaldehyde resin: 7.8 parts;
[0223] Nano-graphene: 4.5 parts;
[0224] Boron nitride: 2.5 parts;
[0225] Thickener: 1.8 parts;
[0226] Deionized water: 220 parts.
[0227] Manufacturing process:
[0228] Step 1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 minutes, then add nano-graphene, boron nitride, and a thickener, stir at a speed of 350 rpm for 2.5 hours, and dry at 88° C. for 3 hours to obtain basic card paper;
[0229] Step 2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after complete dissolution to obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350rpm and 75°C, slowly add chloroacetic acid at a rate of 0.7 ml per minute, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol and dry to obtain carboxymethyl chitosan;
[0230] Step 3: Add polyetheramine and deionized water to a new reactor, stir at a speed of 350 rpm, add carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide obtained in step 2 after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine;
[0231] Step 4: Add epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in step 3 and stir at 250 rpm for 2.5 hours. Immerse the basic card paper obtained in step 1 for 1.8 hours. After taking it out, cure it at 150°C for 2 hours to obtain the finished product.
[0232] The performance test of the high hardness card paper prepared in Examples 1-5 and Comparative Examples 1-4 was carried out, and the test method was as follows:
[0233] 1. Hardness test: Test according to the paper bursting strength test standard (GB / T454-2002). The test results are expressed as bursting index (kPa·m 2 / g) indicates;
[0234] 2. Corrosion resistance test: Soak the card paper sample in a 10% hydrochloric acid solution for 24 hours and observe the surface changes.
[0235] The test results are shown in the following table:
[0236]
[0237] From the above test results, it can be seen that the high-hardness card paper prepared in Examples 1-5 is better than the control example in terms of hardness and corrosion resistance. Among them, Example 4 has the best performance, and its burst resistance index reaches 4.8 kPa·m 2 / g, and there was no obvious change on the surface after immersion in hydrochloric acid solution for 24 hours. Boron nitride was omitted in Control Example 1, nano-graphene was omitted in Control Example 2, nano-graphene and thickener were omitted in Control Example 3, and meta-xylenediamine was omitted in Control Example 4. The absence of these ingredients affected the performance of the card paper to a certain extent.
[0238] In summary, the high-hardness card paper and its manufacturing process provided by the present invention can significantly improve the hardness and corrosion resistance of the card paper by optimizing the raw material formula and process parameters, and has good application prospects.
[0239] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.
Claims
1. A high-hardness card paper, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of pulp, 5-8 parts of chitosan, 28-40 parts of acetic acid, 11-12 parts of acetone, 4-5 parts of sodium hydroxide, 5-6 parts of chloroacetic acid, 16-17 parts of isopropanol, 100 parts of methanol, 5-6 parts of polyetheramine, 1.5-2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 3-4 parts of N-hydroxysuccinimide, 3.5-4 parts of meta-phenylenediamine, 10-11 parts of epoxy resin, 7.5-8 parts of urea formaldehyde resin, 4-5 parts of nano-scale graphene, 2.5-3 parts of boron nitride, 1.5-2 parts of thickener and 200-250 parts of deionized water.
2. The high-hardness card paper according to claim 1, characterized in that: The thickener is composed of coconut diethanolamide, PEG-150 distearate, and fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 1:1:
1.
3. The high-hardness card paper according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 25 parts of pulp, 6 parts of chitosan, 34 parts of acetic acid, 11.5 parts of acetone, 4.5 parts of sodium hydroxide, 5.5 parts of chloroacetic acid, 16.5 parts of isopropanol, 100 parts of methanol, 5.5 parts of polyetheramine, 1.8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 3.5 parts of N-hydroxysuccinimide, 3.8 parts of meta-phenylenediamine, 10.5 parts of epoxy resin, 7.8 parts of urea formaldehyde resin, 4.5 parts of nano-graphene, 2.8 parts of boron nitride, 1.8 parts of thickener and 220 parts of deionized water.
4. The high-hardness card paper according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 28 parts of pulp, 7 parts of chitosan, 38 parts of acetic acid, 11.8 parts of acetone, 4.8 parts of sodium hydroxide, 5.8 parts of chloroacetic acid, 16.8 parts of isopropanol, 100 parts of methanol, 5.8 parts of polyetheramine, 1.9 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 3.8 parts of N-hydroxysuccinimide, 3.9 parts of meta-phenylenediamine, 10.8 parts of epoxy resin, 7.9 parts of urea formaldehyde resin, 4.8 parts of nano-graphene, 2.9 parts of boron nitride, 1.9 parts of thickener and 240 parts of deionized water.
5. A process for manufacturing high-hardness card paper as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Add pulp and deionized water into a reactor, stir at a speed of 400 rpm for 50 min, then add nano-graphene, boron nitride and thickener, stir at a speed of 350 rpm for 2.5 h, and obtain basic card paper after drying; wherein the weight ratio of nano-graphene, boron nitride and thickener is 1:0.8:0.5; S2: Add chitosan and acetic acid into another reaction kettle, add acetone to precipitate after they are completely dissolved, and obtain chitosan acetate; add sodium hydroxide and isopropanol to the chitosan acetate, stir at 350 rpm and 75°C, slowly add chloroacetic acid dropwise, react for 3.5 hours, cool to room temperature, adjust the pH to neutral, wash with methanol, and dry to obtain carboxymethyl chitosan; S3: Add polyetheramine and deionized water to a new reactor, stir at 350 rpm, add carboxymethyl chitosan obtained in S2, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and N-hydroxysuccinimide after complete dissolution, continue stirring to completely dissolve, control the pH of the solution to always remain at 5.8, react for 3.5 hours, dialyze using a dialysis bag for 4 days, and freeze-dry to obtain chitosan-grafted polyetheramine; S4: Add m-phenylenediamine, epoxy resin, urea formaldehyde resin and methanol into the reaction kettle. After they are completely dissolved, add the chitosan grafted polyetheramine obtained in S3 and stir at 250 rpm for 2.5 hours. Immerse the basic card paper obtained in S1 and cure it at 150°C for 2 hours to obtain the finished product.
6. The manufacturing process according to claim 5, characterized in that In S1, the drying temperature is 80-90° C. and the drying time is 3-4 hours.
7. The manufacturing process according to claim 5, characterized in that: In S2, the speed of adding chloroacetic acid is 0.5-0.8 ml per minute.
8. The manufacturing process according to claim 5, characterized in that: In S3, the mass ratio of polyetheramine, carboxymethyl chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide is 1:0.8:0.2:0.
3.
9. The manufacturing process according to claim 5, characterized in that: In S4, the mass ratio of m-xylylenediamine, epoxy resin, urea formaldehyde resin and chitosan grafted polyetheramine is 1:3:2:1.
5.
10. The manufacturing process according to claim 5, characterized in that: In S4, the base card paper is immersed in the mixed solution for 1-2 hours.